Genetic Structure of Natural Northern Range-Margin Mainland, Peninsular, and Island Populations of Northern Red Oak (Quercus rubra L.) - Götz, Jeremias; Rajora, Om P.; Gailing, Oliver (Frontiers in Ecology and Evolution, 2022)
Plant populations at the leading edge of the species’ native range often exhibit genetic structure as a result of genetic drift and adaptation to harsh environmental conditions. Hence, they are likely to harbour rare genetic adaptations to local environmental conditions and therefore are of particular interest to understand climate adaptation. We examined genetic structure of nine northern marginal mainland, peninsular and isolated island natural populations of northern red oak (Quercus rubra), a valuable long-lived North American hardwood tree species, covering a wide climatic range using 17 nuclear microsatellites. We found pronounced genetic differentiation of a disjunct isolated island population from all mainland and peninsular populations. Furthermore, we observed remarkably strong fine-scale spatial genetic structure (SGS) in all investigated populations. Such high SGS values are uncommon and were previously solely observed in extreme range-edge marginal oak populations in one other study. We found a significant correlation between major climate parameters and SGS formation in northern range-edge red oak populations, with more pronounced SGS in colder and drier regions. Most likely, the harsh environment in leading edge populations influences the density of reproducing trees within the populations and therefore leads to restricted overlapping of seed shadows when compared to more central populations. SGS was negatively correlated with effective population size and increased with latitude of the population locations. The significant positive association between genetic distances and precipitation differences between populations may be indicative of isolation by adaptation in the observed range-edge populations. However, this association was not confirmed by a multiple regression analysis including geographic distances and precipitation distances, simultaneously. Our study provides new insights in the genetic structure of long-lived tree species at their leading distribution edge.